Comparative Studies of Co/SBA‐15 Catalysts Synthesized with Different Silica Sources Including Coal Fly Ash for Fischer‐Tropsch Synthesis. Issue 11 (14th March 2023) - Gupta, Pavan K.; Kumar, Vineet; Maity, Sudip; Kishore Gupta, Goutam; Datta, Sudipta; Singh, Arvind; Sengupta, Siddhartha
Abstract: SBA‐15 is synthesized using triblock copolymer Pluronic P123 as the structure directing agent and different silica sources such as tetraethyl orthosilicate (TEOS), sodium metasilicate, coal fly ash (CFA) derived supernatant and a mix of sodium metasilicate, CFA‐derived supernatant for comparative study towards Fischer‐Tropsch synthesis (FTS). The active metal cobalt (15 wt. %) has been impregnated in each support via the wet impregnation technique. The catalysts and supports are characterized by N2 adsorption‐desorption, Field Emission Scanning Electron Microscopy (FESEM), High‐Resolution Transmission Electron Microscopy (HRTEM), X‐ray Diffraction (XRD), X‐ray Energy Dispersion Spectrophotometer (EDX), Fourier Transform Infrared (FTIR), and Temperature Programmed Reduction (TPR). The catalytic performance of synthesized catalysts for the FTS has been investigated in a fixed bed tubular reactor at T=220 °C, P=30 bar, and GHSV=500 h −1 using simulated syngas composition equivalent to coal‐derived syngas using air blown fixed bed gasifier having H2 /CO molar ratio of 2 : 1. The maximum CO conversion and middle distillate (C6 −C20 ) selectivity is observed as 59.2 % and 84.6 % respectively for the catalyst support synthesized from mix of sodium metasilicate and CFA‐derived supernatant. Abstract : This study explores the extraction of silica precursor from CFA to synthesize SBA‐15 for application in FTS. The catalytic activity was evaluated using syngas equivalent to syngas derived from air blown fixed bed coal gasifier. Different silica sources such as tetraethyl orthosilicate, sodium metasilicate, and a mix of sodium metasilicate, CFA derived supernatant were used to synthesize SBA‐15 for comparative study of catalytic activity.